(NrAZGROM(B.s (NmOLODAQ GWARDIQ (B/ (Na(B. (Na(B. (NfADEEW (B; (NAWT(B. (NPREDISL(B. (Nl(B. (NqKIMENKOs - (NfADEEW(B, (NaLEKSANDR aLEKSANDROWI^(B,s 1901-1956; (NqKIMENKO(B, (Nl(B.,s ((NmOSKWA (B:s (NhUDOVESTWENNAQ LITERATURA(B,s, 1971)
(Nw KNIGU WO[LI ROMAN (B"(NrAZGROM(B", (NWOSSOZDA@]IJ(B, (NPO SLOWAM m(B. (NgORXKOGO(B, "(N[IROKU@(B, (NPRAWDIWU@ I TALANTLIWEJ[U@ KARTINU GRAVDANSKOJ WOJNY(B", (NI ROMAN (B"(NmOLODAQ GWARDIQ(B". (NoN POSWQ]EN GEROI^ESKOJ BORXBE KOMSOMOLXCEW(B-(NPODPOLX]IKOW GORODA kRASNODONA PROTIW NEMECKO(B-(NFA[ISTSKIH OKKUPANTOW(B, (NO IH BEZGRANI^NOJ(B, (NNEISSQKAEMOJ L@BWI K rODINEs
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NhUDOVNQ L)QÆTERATURAs)E -- (NrOS)QÆJSXKA LÆTERATURAs)E; (NROS)QÆJSXKA LÆTERATURAs)E